Executing Reconfigurations in Hierarchical Component Architectures - Heinzemann, Christian; Becker, Steffen (Proceedings of the 16th International ACM SigSoft Symposium on Component-Based Software Engineering (CBSE))
Mechatronic systems reconfigure the structure of their software architecture, e.g., to avoid hazardous situations or to optimize operational conditions like minimizing their energy consumption. As software architectures are typically build on components, reconfiguration actions need to respect the component structure. This structure should be hierarchical to enable encapsulated components. While many reconfiguration approaches for embedded real-time systems allow the use of hierarchically embedded components, i.e., horizontal composition, none of them offers a modeling and verification solution to take hierarchical composition, i.e., encapsulation, into account. In this paper, we present an extension to our existing modeling language, MechatronicUML, to enable safe hierarchical reconfigurations. The two main extensions are (a) an adapted variant of the two-phase commit protocol to initiate reconfigurations which maintain component encapsulation and (b) a timed model checking verification approach for instances of our model. We illustrate our approach on a case study in the area of smart railway systems by showing two different use cases of our approach and the verification of their safety properties.

Entwurf kooperativer Verhaltensweisen heterogener Roboter - Buse, Dominik

Entwurf eines datenschutzgerechten Reputationssystems - Lutters, Sascha

Entwicklung und Analyse einer verteilten Speicherverwaltung für dynamische heterogene Speichersysteme - Hilleckes, Hendrik

Entwicklung eines Hybriden Planers zur verhaltensorientierten Selbstoptimierung - Borkowski, Richard

Emulating Wavelength Division Multiplexing using Openflow - Satya, Suhas

Effizienzsteigerung durch gewichtete Produktbewertungen - Reineke, Max

Dynamic One-to-One Matching: Theory and a Job Market Application - Stroh-Maraun, Nadja

Dispersion of Multi-Robot Teams - Heindorf, Stefan

Direct Chosen-Ciphertext Secure Attribute-Based Key Encapsulations without Random Oracles - Blömer, Johannes; Liske, Gennadij
We present a new technique to realize attribute-based encryption (ABE) schemes secure in the standard model against chosen-ciphertext attacks (CCA-secure). Our approach is to extend certain concrete chosen-plaintext secure (CPA-secure) ABE schemes to achieve more efficient constructions than the known generic constructions of CCA-secure ABE schemes. We restrict ourselves to the construction of attribute-based key encapsulation mechanisms (KEMs) and present two concrete CCA-secure schemes: a key-policy attribute-based KEM that is based on Goyal's key-policy ABE and a ciphertext-policy attribute-based KEM that is based on Waters' ciphertext-policy ABE. To achieve our goals, we use an appropriate hash function and need to extend the public parameters and the ciphertexts of the underlying CPA-secure encryption schemes only by a single group element. Moreover, we use the same hardness assumptions as the underlying CPA-secure encryption schemes.

Der Einfluss adaptierter Erwartungen in dynamischen Cournot Oligopolen - Kornhoff, Tobias

Continuous Gossip-based Aggregation through Dynamic Information Aging - Graffi, Kalman; Rapp, Vitaly (Proceedings of the International Conference on Computer Communications and Networks (ICCCN'13))
Existing solutions for gossip-based aggregation in peer-to-peer networks use epochs to calculate a global estimation from an initial static set of local values. Once the estimation converges system-wide, a new epoch is started with fresh initial values. Long epochs result in precise estimations based on old measurements and short epochs result in imprecise aggregated estimations. In contrast to this approach, we present in this paper a continuous, epoch-less approach which considers fresh local values in every round of the gossip-based aggregation. By using an approach for dynamic information aging, inaccurate values and values from left peers fade from the aggregation memory. Evaluation shows that the presented approach for continuous information aggregation in peer-to-peer systems monitors the system performance precisely, adapts to changes and is lightweight to operate.

CONE-DHT: A distributed self-stabilizing algorithm for a heterogeneous storage system - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 27th International Symposium on Distributed Computing (DISC))
We consider the problem of managing a dynamic heterogeneous storagesystem in a distributed way so that the amount of data assigned to a hostin that system is related to its capacity. Two central problems have to be solvedfor this: (1) organizing the hosts in an overlay network with low degree and diameterso that one can efficiently check the correct distribution of the data androute between any two hosts, and (2) distributing the data among the hosts so thatthe distribution respects the capacities of the hosts and can easily be adapted asthe set of hosts or their capacities change. We present distributed protocols forthese problems that are self-stabilizing and that do not need any global knowledgeabout the system such as the number of nodes or the overall capacity of thesystem. Prior to this work no solution was known satisfying these properties.

Comparison of Various Contract-Based Approaches for Specifying Behavior of On-The-Fly Computing Services - Jagannath, Kavitha

Comparative Evaluation of Peer-to-Peer Systems Using PeerfactSim.KOM - Feldotto, Matthias; Graffi, Kalman (Proceedings of the International Conference on High Performance Computing and Simulation (HPCS'13))
Comparative evaluations of peer-to-peer protocols through simulations are a viable approach to judge the performance and costs of the individual protocols in large-scale networks. In order to support this work, we enhanced the peer-to-peer systems simulator PeerfactSim.KOM with a fine-grained analyzer concept, with exhaustive automated measurements and gnuplot generators as well as a coordination control to evaluate a set of experiment setups in parallel. Thus, by configuring all experiments and protocols only once and starting the simulator, all desired measurements are performed, analyzed, evaluated and combined, resulting in a holistic environment for the comparative evaluation of peer-to-peer systems.

Cliquenbildung in verteilten Systemen - Blumentritt, Fritz

Ca-Re-Chord: A Churn Resistant Self-stabilizing Chord Overlay Network - Graffi, Kalman; Benter, Markus; Divband, Mohammad; Kniesburges, Sebastian; Koutsopoulos, Andreas (Proceedings of the Conference on Networked Systems (NetSys))
Self-stabilization is the property of a system to transfer itself regardless of the initial state into a legitimate state. Chord as a simple, decentralized and scalable distributed hash table is an ideal showcase to introduce self-stabilization for p2p overlays. In this paper, we present Re-Chord, a self-stabilizing version of Chord. We show, that the stabilization process is functional, but prone to strong churn. For that, we present Ca-Re-Chord, a churn resistant version of Re-Chord, that allows the creation of a useful DHT in any kind of graph regardless of the initial state. Simulation results attest the churn resistance and good performance of Ca-Re-Chord.

International as Opposed to Domestic New Venturing: The Moderating Role of Perceived Barriers to Internationalization. - Baum, M; Schwens, C; Kabst, Rüdiger (International Small Business Journal (ISBJ).)

Conjoint implications on job preferences: The moderating role of involvement. - Baum, M; Kabst, Rüdiger (International Journal of Human Resource Management (IJHRM).)

Business Process Models - Change Management - Gerth, Christian
In recent years, the role of process models in the development of enterprise software systems has increased continuously. Today, process models are used at different levels in the development process. For instance, in Service-Oriented Architectures (SOA), high-level business process models become input for the development of IT systems, and in running IT systems executable process models describe choreographies of Web Services. A key driver behind this development is the necessity for a closer alignment of business and IT requirements, to reduce the reaction times in software development to frequent changes in competitive markets.Typically in these scenarios, process models are developed, maintained, and transformed in a team environment by several stakeholders that are often from different business units, resulting in different versions. To obtain integrated process models comprising the changes applied to different versions, the versions need to be consolidated by means of model change management. Change management for process models can be compared to widely used concurrent versioning systems (CVS) and consists of the following major activities: matching of process models, detection of differences, computation of dependencies and conflicts between differences, and merging of process models.Although in general model-driven development (MDD) is accepted as a well-established development approach, there are still some shortcomings that let developers decide against MDD and for more traditional development paradigms. These shortcomings comprise a lack of fully integrated and fully featured development environments for MDD, such as a comprehensive support for model change management.In this thesis, we present a framework for process model change management. The framework is based on an intermediate representation for process models that serves as an abstraction of specific process modeling languages and focuses on common syntactic and semantic core concepts for the modeling of workflow in process models. Based on the intermediate representation, we match process models in versioning scenarios and compute differences between process models generically. Further, we consider the analysis of dependencies between differences and show how conflicts between differences can be computed by taking into account the semantics of the modeling language.As proof-of concept, we have implemented major parts of this framework in terms of a prototype. The detection of differences and dependencies contributed also to the Compare & Merge framework for the IBM WebSphere Business Modeler V 7.0 [1] (WBM), which was released as a product in fall 2009.

How to attract applicants in the atlantic versus the asia-pacific region? A cross-national analysis on China, India, Germany, and Hungary. - Baum, M; Kabst, Rüdiger (Journal of World Business (JWB).)

Bootstrapping Skynet: Calibration and Autonomic Self-Control of Structured Peer-to-Peer Networks - Graffi, Kalman; Klerx, Timo (Proceedings of the International Conference on Peer-to-Peer Computing (P2P'13))
Peer-to-peer systems scale to millions of nodes and provide routing and storage functions with best effort quality. In order to provide a guaranteed quality of the overlay functions, even under strong dynamics in the network with regard to peer capacities, online participation and usage patterns, we propose to calibrate the peer-to-peer overlay and to autonomously learn which qualities can be reached. For that, we simulate the peer-to-peer overlay systematically under a wide range of parameter configurations and use neural networks to learn the effects of the configurations on the quality metrics. Thus, by choosing a specific quality setting by the overlay operator, the network can tune itself to the learned parameter configurations that lead to the desired quality. Evaluation shows that the presented self-calibration succeeds in learning the configuration-quality interdependencies and that peer-to-peer systems can learn and adapt their behavior according to desired quality goals.

Gender Effects on Entrepreneurial Intention: A Meta-Analytical Structural Equation Model. - Haus, I; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger (International Journal of Gender and Entrepreneurship (IJGE))

Analyzing observed composite differences across groups: Is partial measurement invariance enough? - Steinmetz, Holger (European Journal of Research Methods for the Behavioral and Social Sciences.)

Beschleunigung von Tiefenberechung aus Stereobildern durch FPGA-basierte Datenflussrechner - Bick, Christian

Bandbreiten-beschränktes Scheduling mit skalierbaren Jobanforderungen in Multiprozessor-Umgebungen - Meschede, Julian

Automated Service Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the 11th International Conference on Service Oriented Computing (ICSOC'13))
In the service-oriented computing domain, the number of available software services steadily increased in recent years, favored by the rise of cloud computing with its attached delivery models like Software-as-a-Service (SaaS). To fully leverage the opportunities provided by these services for developing highly flexible and aligned SOA, integration of new services as well as the substitution of existing services must be simplified. As a consequence, approaches for automated and accurate service discovery and composition are needed. In this paper, we propose an automatic service composition approach as an extension to our earlier work on automatic service discovery. To ensure accurate results, it matches service requests and available offers based on their structural as well as behavioral aspects. Afterwards, possible service compositions are determined by composing service protocols through a composition strategy based on labeled transition systems.

Auktionen im Beschaffungsmanagement - Eine spieltheoretische Analyse - Meckenstock, Kevin

Attributbasierte Verschlüsselung mittels Gittermethoden - Mathematische Grundlagen, Verfahren und Sicherheitsbeweise - Kohn, Kathlén

Asymmetric Nash bargaining solutions and competitive payoffs - Brangewitz, Sonja; Gamp, Jan-Philip (Economics Letters)
We establish a link between cooperative and competitive behavior. For every possible vector of weights of an asymmetric Nash bargaining solution there exists a market that has this asymmetric Nash bargaining solution as its unique competitive payoff vector.

Approximation Algorithms for the Linear Arrangement of Special Classes of Graphs - Setzer, Alexander

Analyse von Benutzeranforderungen von Service-Kompositionen mittels Modelchecking - Nickel, Tobias

An Approach for a Decision Support Systems to optimize Water Tanks in Water Supply Systems by combining Network Reduction, Optimization and Simulation - Hallmann, Corinna
Since the last two decades, the water consumption in Germany is decreasing, which causes the water tanks and pipes in a water supply system to work inefficiently. This paper proposes an approach for a decision support system, which helps to decide how to plan new water tanks and resize existing tanks in water supply systems. The approach uses a combination of network reduction, mathematical optimization and hydraulic simulation. The mathematical optimization model is a nonconvex Mixed Integer Quadratically Constrained Program (MIQCP), which is solved by a piecewise linearization. As this may lead to many binary variables and therefore high computational times, the size of the water supply system model is reduced before building the optimization model. By applying several network reduction techniques there may occur some hydraulic differences between the original network model and the reduced network model. To make sure that the solution obtained in the optimization process is feasible in the original water supply system, the solution is verified by a hydraulic simulation tool.

Assignments of Collaborative Rescue Units during Emergency Response - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Journal of Information Systems for Crisis Response and Management)

Decision Modeling for Assignments of Collaborative Rescue Units during Emergency Response - Wex, Felix; Schryen, Guido; Neumann, Dirk (Proceedings of the 46th Hawaii International Conference on System Science)

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, Philip; Graffi, Kalman (Proceedings of the Conference on Networked Systems (NetSys))
Distributed hash tables are very versatile to use, as distributed storage is a desirable feature for various applications. Typical structured overlays like Chord, Pastry or Kademlia consider only homogeneous nodes with equal capacities, which does not resemble reality. In a practical use case, nodes might get overloaded by storing popular data. In this paper, we present a general approach to enable capacity awareness and load-balancing capability of homogeneous structured overlays. We introduce a hierarchical second structured overlay aside, which allows efficient capacity-based access on the nodes in the system as hosting mirrors. Simulation results show that the structured overlay is able to store various contents, such as of a social network, with only a negligible number of overloaded peers. Content, even if very popular, is hosted by easily findable capable peers. Thus, long-existing and well-evaluated overlays like Chord or Pastry can be used to create attractive DHT-based applications.

A Survey of Fuzzy Service Matching Approaches in the Context of On-The-Fly Computing - Platenius, Marie; von Detten, Markus; Becker, Steffen; Schäfer, Wilhelm; Engels, Gregor (Proceedings of the 16th International ACM Sigsoft Symposium on Component-Based Software Engineering)
In the last decades, development turned from monolithic software products towards more flexible software components that can be provided on world-wide markets in form of services. Customers request such services or compositions of several services. However, in many cases, discovering the best services to address a given request is a tough challenge and requires expressive, gradual matching results, considering different aspects of a service description, e.g., inputs/ouputs, protocols, or quality properties. Furthermore,in situations in which no service exactly satifies the request, approximate matching which can deal with a certain amount of fuzziness becomes necessary. There is a wealth of service matching approaches, but it is not clear whether there is a comprehensive, fuzzy matching approach which addresses all these challenges. Although there are a few service matchingsurveys, none of them is able to answer this question. In this paper, we perform a systematic literature survey of 35 (outof 504) service matching approaches which consider fuzzy matching. Based on this survey, we propose a classication,discuss how different matching approaches can be combined into a comprehensive matching method, and identify future research challenges.

A privacy-friendly Architecture for future Cloud Computing - Petrlic, Ronald; Sekula, Stephan; Sorge, Christoph (International Journal of Grid and Utility Computing)
We present a privacy-friendly architecture for a future cloud computing scenario where software licensing and software payment plays a major role. We show how digital rights management as a technical solution for software licensing can be achieved in a privacy-friendly manner. In our scenario, users who buy software from software providers and execute it at computing centres stay anonymous. At the same time, our approach guarantees that software licenses are bound to users and that their validity is checked before execution. Thus, DRM constitutes an incentive for software providers to take part in such a future cloud computing scenario. We employ a software re-encryption scheme so that computing centres are not able to build profiles of their users – not even under a pseudonym. We make sure that malicious users are unable to relay software to others.

A Local Heuristic for Latency-Optimized Distributed Cloud Deployment - Keller, Matthias; Pawlik, Stefan; Pietrzyk, Peter; Karl, Holger (Proceedings of the 6th International Conference on Utility and Cloud Computing (UCC) workshop on Distributed cloud computing)
In Distributed Cloud Computing, applications are deployed across many data centres at topologically diverse locations to improved network-related quality of service (QoS). As we focus on interactive applications, we minimize the latency between users and an application by allocating Cloud resources nearby the customers. Allocating resources at all locations will result in the best latency but also in the highest expenses. So we need to find an optimal subset of locations which reduces the latency but also the expenses – the facility location problem (FLP). In addition, we consider resource capacity restrictions, as a resource can only serve a limited amount of users. An FLP can be globally solved. Additionally, we propose a local, distributed heuristic. This heuristic is running within the network and does not depend on a global component. No distributed, local approximations for the capacitated FLP have been proposed so far due to the complexity of the problem. We compared the heuristic with an optimal solution obtained from a mixed integer program for different network topologies. We investigated the influence of different parameters like overall resource utilization or different latency weights.

A Distributed Approximation Algorithm for Strongly Connected Dominating-Absorbent Sets in Asymmetric Wireless Ad-Hoc Networks - Markarian, Christine; Meyer auf der Heide, Friedhelm; Schubert, Michael (Proceedings of the 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics (ALGOSENSORS))
Dominating set based virtual backbones are used for rou-ting in wireless ad-hoc networks. Such backbones receive and transmit messages from/to every node in the network. Existing distributed algorithms only consider undirected graphs, which model symmetric networks with uniform transmission ranges. We are particularly interested in the well-established disk graphs, which model asymmetric networks with non-uniform transmission ranges. The corresponding graph theoretic problem seeks a strongly connected dominating-absorbent set of minimum cardinality in a digraph. A subset of nodes in a digraph is a strongly connected dominating-absorbent set if the subgraph induced by these nodes is strongly connected and each node in the graph is either in the set or has both an in-neighbor and an out-neighbor in it. We introduce the first distributed algorithm for this problem in disk graphs. The algorithm gives an O(k^4) -approximation ratio and has a runtime bound of O(Diam) where Diam is the diameter of the graph and k denotes the transmission ratio r_{max}/r_{min} with r_{max} and r_{min} being the maximum and minimum transmission range, respectively. Moreover, we apply our algorithm on the subgraph of disk graphs consisting of only bidirectional edges. Our algorithm gives an O(ln k) -approximation and a runtime bound of O(k^8 log^∗ n) , which, for bounded k , is an optimal approximation for the problem, following Lenzen and Wattenhofer’s Ω(log^∗ n) runtime lower bound for distributed constant approximation in disk graphs.

Revisiting IS Business Value Research: What we already know, what we still need to know, and how we can get there - Schryen, Guido (European Journal of Information Systems (EJIS))

A Deterministic Worst-Case Message Complexity Optimal Solution for Resource Discovery - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of 20th International Colloqium on Structural Information and Communication Complexity (SIROCCO))
We consider the problem of resource discovery in distributed systems. In particular we give an algorithm, such that each node in a network discovers the add ress of any other node in the network. We model the knowledge of the nodes as a virtual overlay network given by a directed graph such that complete knowledge of all nodes corresponds to a complete graph in the overlay network. Although there are several solutions for resource discovery, our solution is the first that achieves worst-case optimal work for each node, i.e. the number of addresses (O(n)) or bits (O(nlogn)) a node receives or sendscoincides with the lower bound, while ensuring only a linearruntime (O(n)) on the number of rounds.

Exploring Intermediate Vocational Education and Training for 16-19 Year-olds in Germany and England - Higham, J. J. S.; Kremer, H.-Hugo; Yeomans, D. (The Architecture of Innovative Apprenticeship)

Lernen im Justizvollzug. Vorstellung und Grundidee des Modellprojektes TANDEM - Kremer, H.-Hugo; Beutner, Marc; Wirth, W. (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

Berufsorientierung im Jungtätervollzug - Rahmenkonzept und übergreifenden Prinzipien - Kremer, H.-Hugo; Beutner, Marc (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

myflux.eu - Ein Instrument zur Förderung von Zielorientierung, Reflexion und Verantwortung im Berufsorientierungsprozess von Jungtätern - Gebbe, M.; Kremer, H.-Hugo (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

Stärkenbasierte Berufsorientierung im Jungtätervollzug - Kremer, H.-Hugo; Knust, S. (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

Mit dem Tandem in die Zukunft - Eine Einschätzung aus berufs- und wirtschaftspädagogischer Perspektive - Kremer, H.-Hugo; Beutner, Marc (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

Influence of angular radiated ultrasound waves on the Schlieren tomogram - Olfert, Sergei; Claes, Leander; Henning, Bernd (Proceedings of the International Conference on Acoustics)